The effect of propofol on the proliferation and apoptosis of hepatocellular carcinoma cells through TGF-Β1/Smad2 signaling pathway. Issue 1 (1st January 2021) - Li, Zongchao; Liu, Honglei; Zhang, Yunxiao; Tan, Hongyu
ABSTRACT: Malignant tumors are a serious threat to human health. Surgical resection is the most effective treatment for liver cancer. However, liver cancer is mostly found at an advanced stage, is difficult to remove by surgery, and has a very high recurrence rate after surgery. The current liver cancer treatment drugs have serious side effects, and the treatment effect is not ideal, far from meeting the clinical needs. Based on this, this paper studies the effect of propofol on the proliferation and apoptosis of liver cancer cells through the TGF-B1/Smad2 signaling pathway, and explores the proliferation, adhesion and apoptosis of cancer cells in patients with propofol. This paper uses a comparative experiment. With medical imaging method, 80 rats with liver cancer in the same period were cultured. High-precision microscope and radiolocation method were used to observe and record the whole process of propofol regulating Smad2 signal pathway. The results show that propofol can effectively inhibit the proliferation of cancer cells in patients with liver cancer. Propofol can increase the activity and content of transforming growth factor-β1 by 12% and 20%, respectively, and then inhibit the proliferation rate of liver cancer cells by 10% through the Smad2 signaling pathway, and exponentially increase the apoptotic number of liver cancer cells. This shows that propofol has a significant inhibitory effect on the cycle of liver cancer cells. Under the action of propofol, the life cycle of liver cancer cells is shortened, which provides a certain theoretical basis for the treatment of liver cancer. GRAPHICAL ABSTRACT: uf0001